Finite‐element calculation of electromagnetic characteristics and steady‐state stability of dual‐excited synchronous generator. Issue 10 (4th June 2021) - Xu, Guorui; Wang, Zhenzhen; Liu, Bingchen; Zhan, Yang; Li, Weili; Zhao, Haisen; Huang, Hao; Yu, Honghao
Abstract: The Dual‐Excited Synchronous Generator (DESG) has two sets of field windings. The magnitudes and directions of the two field currents can be regulated, so that the excitation magneto‐motive force can be in any direction. The electromagnetic characteristics of the DESG may be different with those of the Traditional Synchronous Generator (TSG) for the different rotor structures of the two generators. To obtain better electromagnetic characteristics, a time‐stepping finite element model (T‐S FEM) of the DESG is established. The air‐gap radial flux density, saturation, active and reactive power of the DESG in single‐ and dual‐axis excitation modes are calculated and compared with those of the TSG. The electromagnetic characteristics affected by the different ratio of q‐axis field current to d‐axis field current are studied. On this basis, an excitation control strategy that can enhance the steady‐state stability is proposed, and the steady‐state stability limits with and without excitation control are calculated by the T‐S FEM. A 10‐kW DESG is developed to verify the correctness of the simulation results. The results show that the DESG with dual‐axis excitation has better electromagnetic characteristics and stronger reactive power ability, and the steady‐state stability limit of the DESG is increased obviously through the excitation control.